2016
DOI: 10.3892/mmr.2016.5426
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin reverses intrinsic and acquired drug resistance to cisplatin through the AKT signaling pathway in gastric cancer cells

Abstract: Cisplatin is the most common chemotherapeutic agent for gastric cancer (GC), however it activates AKT, which contributes to intrinsic and acquired resistance. Bufalin, a traditional Chinese medicine, shows significant anticancer activity by inhibiting the AKT pathway. It was therefore hypothesized that bufalin could counteract cisplatin resistance in GC cells. SGC7901, MKN‑45 and BGC823 human GC cells were cultured under normoxic and hypoxic conditions. Effects of cisplatin and bufalin on GC cells were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Previous studies revealed that MAPK signaling pathway activation serves key roles in drug resistance, notably in gastric cancer, breast cancer, prostate cancer and CRC. The PI3K/AKT/mTOR pathway also regulates cancer progression and is recognized as a major cause of multidrug resistance in various types of cancer (15)(16)(17)(18). This pathway has also been identified as a potent contributor to drug resistance in CRC, particularly resistance to 5-FU and oxaliplatin (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that MAPK signaling pathway activation serves key roles in drug resistance, notably in gastric cancer, breast cancer, prostate cancer and CRC. The PI3K/AKT/mTOR pathway also regulates cancer progression and is recognized as a major cause of multidrug resistance in various types of cancer (15)(16)(17)(18). This pathway has also been identified as a potent contributor to drug resistance in CRC, particularly resistance to 5-FU and oxaliplatin (35).…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin plus 5-FU regimen resistance is subsequently induced via the activation of the PI3K/AKT, MAPK and Janus kinase/signal transducer and activator of transcription (JAK-STAT) signaling pathways. In addition, it has been reported that the MAPK (12)(13)(14) and PI3K/AKT/mTOR (15)(16)(17)(18) pathways serve key roles in drug resistance, notably in CRC, and that PI3K/AKT signaling pathway inhibition can reduce resistance to chemotherapeutic drugs. It was also reported that survivin overexpression, which may be a downstream effect of the MAPK or PI3K-AKT-mTOR signaling pathway (19), is associated with drug resistance in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…We found that drug resistance was higher in STSCs cis than in their parent cells, which proved that cisplatin could induce acquired drug resistance. In view of the inhibiting stemness and acquired drug-resistance effects (23), we speculated that bufalin could inhibit acquired cisplatin resistance in CRC cells via the inhibition of stemness. We found that the combination of bufalin and cisplatin could inhibit proliferation and induce apoptosis in STSCs cis in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, bufalin was shown to possess high anticancer ability in various cancers (2024). The anticancer mechanisms of bufalin can be summarized as: inhibition of proliferation (20), promotion of apoptosis (24), inhibition of angiogenesis and metastasis (21), reversal of drug resistance (23), and induction of autophagy (25). Recent studies have suggested that bufalin inhibits differentiation, proliferation, and drug resistance in cancers via the inhibition of stemness (2628).…”
Section: Introductionmentioning
confidence: 99%
“…For example, bufalin can inhibit cancer cell proliferation [ 5 , 6 ], induce cancer cell apoptosis and autophagy [ 7 , 8 ], inhibit cancer metastasis and invasion [ 9 , 10 ], and reverse multidrug resistance [ 11 ]. Studies had found that bufalin inhibits GC proliferation, induces apoptosis, and reverses cisplatin resistance [ 12 , 13 ]. However, the anti-invasion and anti-metastasis activity of bufalin in GC is still not clear.…”
Section: Introductionmentioning
confidence: 99%